MUHAMMADIYAH: CONTESTING IDEOLOGIES BETWEEN PROGRESSIVE ISLAM AND TRADITIONAL - Mursalim Munir; Usman Jafar; Barsihannor Barsihannor (JICSA : Journal of Islamic Civilization in Southeast Asian, 2020)
The research focuses on examining the dynamics of variants of Islamic thought in Muhammadiyah, especially progressive Islamic thought and conservative Islam. The main objective of this research is to identify how the contestation model of the two variants strengthens its hegemony. To achieve this goal, library research was carried out using qualitative-descriptive-analytical methods and utilizing two approaches, namely historical perspectives and sociological knowledge. Based on the available literature, it is found that two tendencies of thought in Muhammadiyah, namely Progressive Islamic thought and Conservative Islam, contradict each other in areas which in the context of Muhammadiyah are closely related to the ideological dimension, namely the methodology of thought and thought construction. Contestation in this aspect has implications for the emergence of a more practical contestation, namely the efforts to market their ideas and beliefs through organizational structural and cultural channels outside the organizational authority.